2011
DOI: 10.1071/ch11156
|View full text |Cite
|
Sign up to set email alerts
|

Progress Toward Robust Polymer Hydrogels

Abstract: In this review we highlight new developments in tough hydrogel materials in terms of their enhanced mechanical performance and their corresponding toughening mechanisms. These mechanically robust hydrogels have been developed over the past 10 years with many now showing mechanical properties comparable with those of natural tissues. By first reviewing the brittleness of conventional synthetic hydrogels, we introduce each new class of tough hydrogel: homogeneous gels, slip-link gels, double-network gels, nanoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
260
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 271 publications
(265 citation statements)
references
References 110 publications
5
260
0
Order By: Relevance
“…The obtained noncovalent cross-linked hydrogels usually present a high degree of toughness. However, the stiffness of noncovalent cross-linked hydrogels is significantly lower than covalent cross-linked ones (Sun et al, 2012;Haque et al, 2011;Naficy et al, 2011). Noncovalent cross-linked hydrogels can then not be used in load bearing biomedical applications, where a high degree of stiffness and toughness are simultaneously needed.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained noncovalent cross-linked hydrogels usually present a high degree of toughness. However, the stiffness of noncovalent cross-linked hydrogels is significantly lower than covalent cross-linked ones (Sun et al, 2012;Haque et al, 2011;Naficy et al, 2011). Noncovalent cross-linked hydrogels can then not be used in load bearing biomedical applications, where a high degree of stiffness and toughness are simultaneously needed.…”
Section: Introductionmentioning
confidence: 99%
“…The inventions of several strong and tough hydrogels in the early 2000s have greatly expanded the potential possibility of this material [9][10][11][12][13] and initiated many researches to develop high strength hydrogels. [14][15][16][17][18][19][20][21] These studies have also stimulated the fundamental researches on the fracture mechanics of soft and wet materials. [22][23] Studies on the double-network (DN) gels, one of the toughest hydrogels consisting of interpenetrating brittle and ductile networks, have indicated that the internal rupture of the brittle network, which effectively dissipates energy and prevents catastrophic crack propagation upon loading, gives the extraordinarily high toughness.…”
Section: Introductionmentioning
confidence: 99%
“…Until quite recently, synthetically produced hydrogels were notoriously brittle and applications somewhat limited 1 . In the past decade or so, several new tough hydrogels have been introduced that have opened up the possibility of new applications, particularly in biomedicine.…”
Section: Introductionmentioning
confidence: 99%